2003
DOI: 10.1097/00000478-200305000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons of Outcome and Prognostic Features Among Histologic Subtypes of Renal Cell Carcinoma

Abstract: Our objective was to compare cancer-specific survival and to examine associations with outcome among the histologic subtypes of renal cell carcinoma (RCC). We studied 2385 patients whose first surgery between 1970 and 2000 was a radical nephrectomy for sporadic, unilateral RCC. All RCC tumors were classified following the 1997 Union Internationale Contre le Cancer and American Joint Committee on Cancer guidelines. There were 1985 (83.2%) patients with clear cell, 270 (11.3%) with papillary, 102 (4.3%) with chr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

27
629
10
25

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 973 publications
(706 citation statements)
references
References 16 publications
27
629
10
25
Order By: Relevance
“…In comparison, Mikami et al (2006) reported less ETS-1 expression and vascularization in papillary carcinoma compared to clear cell carcinoma. Furthermore, a better prognosis for patients with renal papillary carcinoma than for patients with renal clear cell carcinoma has been described by Cheville et al (2003). Whether a worse prognosis for patients might be due to a WT1-dependent upregulation of ETS-1 and subsequent increased vascularization cannot be answered at present, but the use of inducible WT1 conditional knockout mice in tumour models (currently under investigation) will shed light into the role of WT1 for tumour angiogenesis in vivo.…”
Section: Wt1 Activates Ets-1 In Endothelial Cellsmentioning
confidence: 99%
“…In comparison, Mikami et al (2006) reported less ETS-1 expression and vascularization in papillary carcinoma compared to clear cell carcinoma. Furthermore, a better prognosis for patients with renal papillary carcinoma than for patients with renal clear cell carcinoma has been described by Cheville et al (2003). Whether a worse prognosis for patients might be due to a WT1-dependent upregulation of ETS-1 and subsequent increased vascularization cannot be answered at present, but the use of inducible WT1 conditional knockout mice in tumour models (currently under investigation) will shed light into the role of WT1 for tumour angiogenesis in vivo.…”
Section: Wt1 Activates Ets-1 In Endothelial Cellsmentioning
confidence: 99%
“…One third of the RCC patients develop metastasis at presentation with a poor 5-year survival because there is no early warning sign [3]. At least five types of RCC were found, and the majority (>80%) are classified as clear cell RCC (ccRCC) [4].…”
Section: Introductionmentioning
confidence: 99%
“…1 The most common histological RCC subtype is the conventional or clear cell carcinoma (ccRCC), which accounts for 70-75% of cases. 2,3 At least 60% of ccRCCs have deletions or translocations involving the short arm of chromosome 3, which contains the von Hippel-Lindau (VHL) gene at 3p25. 4,5 The second most common cytogenetic abnormality associated with ccRCC is a gain of chromosome 5q 6 ; however, very little is known about its effects.…”
mentioning
confidence: 99%